Innovation Learning of Tahfid Al-Qur’an Through Classical Method - Eka Prasetiawati; Wiwied Pratiwi; Mispani Mispani (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2018)
Innovation learning of classical Al-Qur'an at TMI Roudhatul Qur’an was very important. Because it was an effort to maintain the al-Qur'an originality for the young generation. The aim of this study was to observe how the learning process of the Tahfidzul Qur'an in using of classical methods. The type of this research was field research. This study used a qualitative analytical descriptive approach, namely the data obtained by interview, observation, and documentation. The results showed that the classical methods in Roudhatul Qur’an of Junior High School were very suitable to be applied because the learning process becomes more efficient and improves the quality of memorization and correcting. Key words: Learning Innovation, Tahfidz Al-Qur'an, Classical Method